Autonomous Learning among EFL Undergraduate Students in Selected Private Indonesian Islamic University: Voices and Activities - Khulaifiyah, Khulaifiyah; Anugerahwati, Mirjam; Widiati, Utami (REiLA : Journal of Research and Innovation in Language, 2022)
Learner autonomy has recently been recognised as an essential component of changes in higher education. The word 'LA' can be misunderstood because it may be viewed differently in various settings. Hence, this study explores whether the students at higher levels of education in Indonesia have better perceptions and efforts to enhance their autonomous learning. Questionnaires and interviews were asked with EFL students in collecting the data. The study sample consisted of 95 students randomly selected from FTTE Islamic University of Riau. This study applied a mix-method, and descriptive statistical testing was employed to analyse the data and determine the research questions. NVivo 12 explored how the students perceived the autonomous learning process. The result showed that the EFL learners mostly perceive autonomous learning as independent learning under one’s target, involving personal learning styles and strategies with the teacher's assistance. A significance value (p) was obtained at the time of initiation, monitoring, and evaluation of the data, respectively 0.286; 0.533; 0.744. So, all the p-value was >0.05. It requires no significant effort in initiating, monitoring, and evaluating among different levels. In addition, there was no significant difference between the efforts of the initiating, monitoring, and evaluating activity performed among EFL learners either in the second, fourth, or sixth level. This point is that EFL learners are not independent in selecting when and how to initiate, monitor, and evaluate autonomous learning. So, this fact shows us that the higher semester level did not guarantee better effort toward autonomous learning activities.